Repercussions of the Spanish War of 1808 on Great Britain - Charles J. ESDAILE (Cuadernos Dieciochistas)
In Great Britain the news that Spain had risen in revolt against the forces of Napoleon Bonaparte became the sensation of the year. Brought in the first instance by a delegation sent from the province of Asturias by its traditional assembly, it gave rise to a great wave of joy and excitement that found expression bothin the press and in the actions of the Tory government of Lord Portland, which immediately decided to send an expeditionary force to succour the Patriot cause. It was a moment of real national unity: despite their increasing misgivings with respect to the war against Napoleon, even the opposition Whigs shared in the general jubilation. This article examines the reasons for this phenomenon, and argues that they were founded more on the desperate military, political and economic situation in which the British found themselves than on a realistic appreciation of the capacities of the Spanish insurgents. From disillusionment to which the hope of June 1808 gave way, there stemmed many of the problems that so troubled Anglo-Spanish relations IN the six years of war that followed.